QUALITY SERVICE AND THE SATISFACTION OF THE USER AT THE DANCE ACADEMY FITNESS DANCE, PUCALLPA, 2017 - Ramírez Zumaeta, Lila (2019)
The present research work is an undergraduate thesis that aimed to determine the relationship between quality service and user satisfaction of the dance fitness academy of the city of Pucallpa; referring to five dimensions and 9 indicators of the variable: Quality service, as well as the four dimensions and 12 indicators of the variable: User satisfaction. The design used was the descriptive correlational. Applying the statistics, it was determined that there is a relationship between the quality service and user satisfaction of the dance fitness academy of the city of Pucallpa, 2017, which was reflected in the increase in users, r = 0.90 was obtained. positive high, and p value = 0.037 <0.05, that is, the null hypothesis is rejected and it is concluded: There is a relationship between the quality service and user satisfaction of the Dance Dance Academy of the city of Pucallpa, 2017. On the other hand, there were also responses that were inclined to the value totally in disagreement, which do not influence the results. KEYWORDS: service, quality, satisfaction, user